Clinical and functional aspects of work-related musculoskeletal disorders among active workers Aspectos clínicos e funcionais de distúrbios músculo-esqueletais entre trabalhadores ativos - Isabel A P Walsh; Jorge Oishi; Helenice J C Gil Coury (Universidade de São Paulo, 2008)
OBJECTIVE: To evaluate musculoskeletal disorders among active industrial workers. METHODS: The study was carried out in São Carlos, Southeastern Brazil, in 2005. One hundred and thirty-four female workers were physically evaluated and answered questions about their physical symptoms, filled out a pain scale and gave responses in the Oswestry Disability Questionnaire, and the Work Ability Index questionnaire. The data were analyzed descriptively, and in correlation tests and through applying logistic regression. The outcome was evaluated in relation to the perceptions of pain, symptoms, physical assessment, ability to work and disability. RESULTS: Clinical evaluations and sick leave presented positive correlations with the subjective variables. The Work Ability Index presented a negative correlation with the physical disability index (r=-0.69). Symptoms reported at the time of the assessment presented a good correlation with the results from the pain scale and the clinical findings. Previous sick leave showed an association with disability (OR=1.13; 95% CI:1.08;1.18). CONCLUSION: Symptom reports and pain scales may be useful for assessing current conditions at the time of evaluating individuals with work-related musculoskeletal disorders, as they are easier to apply. In more severe cases of such injuries, clinical and functional evaluations and questionnaires such as those relating to ability to work and disability are preferable. Precise and specific evaluations of these disorders may contribute towards fairer legal and administrative decisions. OBJETIVO: Avaliar os distúrbios osteomusculares entre trabalhadores ativos da indústria. MÉTODOS: O estudo foi realizado em São Carlos, SP, em 2005. Cento e trinta e quatro trabalhadoras foram fisicamente avaliadas e responderam a questões sobre sintomas físicos, escala de dor e aos questionários: de Incapacidade Oswestry e o Índice de Capacidade para o Trabalho. Os dados foram analisados descritivamente, em testes de correlação e regressões foram aplicados. O desfecho foi avaliado em relação à percepção de dor, sintomas, avaliação física, capacidade para o trabalho e incapacidade. RESULTADOS: Avaliações clínicas e afastamentos apresentaram correlações positivas com os aspectos subjetivos avaliados. O índice de capacidade para o trabalho apresentou correlação negativa com o índice de incapacidade física (r=-0,69). Sintomas no momento da avaliação apresentaram boa correlação com resultados da escala de dor e achados clínicos. Afastamentos prévios mostraram associação com incapacidade (OR=1,13; IC 95%:1,08;1,18). CONCLUSÕES: Relato de sintomas e escala de dor podem ser úteis para avaliar condições presentes no momento da avaliação em indivíduos com distúrbios osteomusculares relacionados ao trabalho, pois são mais simples de aplicar. Em casos mais severos de lesões, avaliações clínicas e funcionais e questionários, tais como capacidade para o trabalho e incapacidade são preferíveis. Avaliações precisas e específicas desses distúrbios podem contribuir para decisões administrativas e legais mais justas.